Synthesis, in Vivo and in Silico Studies of N-Aryl-4-(1,3-Dioxoisoindolin-2-Yl)Benzamides as an Anticonvulsant Agent - Parisa Kiminejad Malaie; Mehdi Asadi; Faezeh Sadat Hosseini; Mahmood Biglar; Massoud Amanlou (Tabriz University of Medical Sciences, 2020)
Background: These days epilepsy is a common neurological disorder, which can affect on quality of life by unpredictable seizure. Thalidomide is one of the drugs to control the epilepsy but side effects such as teratogenicity, made it difficult to use. Methods: Six new analogues of N-aryl-4-(1,3-dioxoisoindolin-2-yl)benzamides were synthesized and tested for anti-seizure activity. To evaluate the anti-seizure activity of these new derivatives, 40 mice in 8 groups were received 10 mg/Kg of each new derivatives 30 min before the injection of pentylenetetrazole (PTZ, 70 mg/kg) to induced seizures. Latency time to first symptom of seizure was measured and compared to vehicle and standard groups. Docking methodology was applied to study on mode of interaction between GABAA receptor and synthetized compounds.Results: Structures of the all synthesized compounds were confirmed by NMR and mass spectroscopy. The latency time and mortality rate were individually measured for an hour after injection of pentylenetetrazole. Docking study revealed that synthesized compounds and thalidomide interact in similar conformation with GABAA receptor.Conclusion: The experimental and docking results were found in good correlation and demonstrated that the most active compound (5a), with 3,4-dimethylphenyl residue increased the duration of seizure inhibition threshold in comparison with thalidomide.